Design, synthesis and anti-P. falciparum activity of pyrazolopyridine–sulfonamide derivatives. Issue 18 (15th September 2016) - Silva, Thais B.; Bernardino, Alice M.R.; Ferreira, Maria de Lourdes G.; Rogerio, Kamilla R.; Carvalho, Leonardo J.M.; Boechat, Nubia; Pinheiro, Luiz C.S.
Graphical abstract: Abstract: Ten 1-phenyl-1 H -pyrazolo[3, 4- b ]pyridine derivatives connected by a linker group to benzenesulfonamide moieties with different substituents in the 4-position were synthesized and assayed against Plasmodium falciparum . These ten compounds exhibited activity in vitro against the chloroquine-resistant clone W2 with IC50 values ranging from 3.46 to 9.30 μM. The most active derivatives with substituent R2 = Cl or CH3 at the benzenesulfonamide moiety exhibited the lowest IC50 . Compounds with an R1 = CO2 Et substituent at the 5-position of the 1 H -pyrazolo[3, 4- b ]pyridine ring presented lower activity than those with a CN substituent. The 1 H -pyrazolo[3, 4- b ]pyridine system appears to be promising for further studies as an antimalarial for overcoming the burden of resistance in P. falciparum .